Cultural differences in the relations between expressive flexibility and life satisfaction over time - Ang, Jen Ying Zhen; Tsai, William (Frontiers in Psychology, 2023)
Background: Expressive flexibility refers to the ability to assess situational demands and adjust one's emotion expressions via enhancement or suppression. It has been associated with lower levels of depressive and anxiety symptoms and greater social acceptance. These relationships, however, have not yet been examined across cultures -where prior research has found cultural differences in norms on emotion displays and their associations with mental health. This study examined expressive flexibility across three cultural groups and their associations with life satisfaction and depressive symptoms over time. Methods: 276 first-year college students ( 146Asian American, 71 European Americans, 62 Latinx Americans) completed two online surveys during the 1 st (T1) and 13 th week (T2) of the Fall 2020 academic semester. Results: Results revealed no significant cultural group differences in the ability to enhance or suppress emotions.However, we found a significant ethnicity x enhancement ability interaction in predicting T2 life satisfaction, controlling for T1 life satisfaction, age, gender, and emotion regulation frequency. Specifically, greater ability to enhance one's emotions was significantly associated with higher life satisfaction over time among Asian Americans, but not for European Americans and Latinx Americans. Discussion: Our findings illustrate the importance of not looking just at cultural group differences in the levels of expressive flexibility, but also at the associations between expressive flexibility and mental health.